2013
DOI: 10.1063/1.4789756
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of numerical study on thermoelectric-based heating in an integrated centrifugal microfluidic platform for polymerase chain reaction amplification

Abstract: A comprehensive study involving numerical analysis and experimental validation of temperature transients within a microchamber was performed for thermocycling operation in an integrated centrifugal microfluidic platform for polymerase chain reaction (PCR) amplification. Controlled heating and cooling of biological samples are essential processes in many sample preparation and detection steps for micrototal analysis systems. Specifically, the PCR process relies on highly controllable and uniform heating of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In a microfluidic centripetal (centrifugal) device (MCD; also designated as lab-on-a-CD due to the overall structure of most devices), fluids are displaced between chambers and/or reservoirs through microchannels (generally <100 μm in diameter or width) using the centrifugal force generated by rotating the device (reviewed in [ 45 , 46 , 53 , 54 ]). In a MCD, the transfer of microfluids is generally controlled by passive (hydrophilic, hydrophobic, or siphon) valves; a notable exception came in the form of ice valves implemented in the device described by Amasia and colleagues, to constrain a PCR reaction mixture during thermal cycling [ 55 , 56 ]. By design, it is possible to create various types of channels, chambers, and valves which can timely execute a bioanalytical process onboard the device, taking advantage of the fact that a MCD platform does not require an external pumping system.…”
Section: Microfluidics From Paper-based Tests To the Innovative Gmentioning
confidence: 99%
“…In a microfluidic centripetal (centrifugal) device (MCD; also designated as lab-on-a-CD due to the overall structure of most devices), fluids are displaced between chambers and/or reservoirs through microchannels (generally <100 μm in diameter or width) using the centrifugal force generated by rotating the device (reviewed in [ 45 , 46 , 53 , 54 ]). In a MCD, the transfer of microfluids is generally controlled by passive (hydrophilic, hydrophobic, or siphon) valves; a notable exception came in the form of ice valves implemented in the device described by Amasia and colleagues, to constrain a PCR reaction mixture during thermal cycling [ 55 , 56 ]. By design, it is possible to create various types of channels, chambers, and valves which can timely execute a bioanalytical process onboard the device, taking advantage of the fact that a MCD platform does not require an external pumping system.…”
Section: Microfluidics From Paper-based Tests To the Innovative Gmentioning
confidence: 99%
“…Especially for plant samples, liquid nitrogen needs during grinding, and the entire process is time consuming and complicated. Exploiting microfluidic chips in nucleic acid analysis can greatly reduce reagent consumption, shorten assay time and realize precise temperature [18,19]. In the recent decades, microfluidic chips for nucleic acid analysis are mainly concentrated in biomedicine and pointof-care test (POCT) [20,21], but there are few studies in plants, especially in the detection of mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Contact heating has since been used for effective and fast PCR thermocycling by Amasia et al, who used a stationary disc and ice valves for vapor-tight sealing of the PCR chamber during thermocycling. 16,130 The design by Amasia et al used thermoelectric elements for heating, cooling, and valving (shown in Fig. 19).…”
Section: Thermocycling For Na Amplificationmentioning
confidence: 99%